BIOETHANOL PRODUCTION FROM SEAWEED PROCESSING WASTE BY SIMULTANEOUS SACCHARIFICATION AND FERMENTATION (SSF) - Andi Hakim; Ekowati Chasanah; Uju Uju; Joko Santoso (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2017)
Seaweed processing waste has been used for bioethanol production through simultaneous saccharification and fermentation (SSF). SSF is commonly used for bioethanol production to shorten the process and to increase the yield of ethanol produced by Trichoderma reesei and Saccharomyces cerevisiae. The aim of this research was to obtain the best concentration of T. reesei and S. cerevisiae to produce bioethanol by SSF. The concentration of T. reesei and S. cerevisiae used was 0 (control), 5, 10, 15 and 20% (v/v). The SSF process was carried out by using shaking incubator at 35 °C and rotation of 150 rpm for 3 days. The untreated and hot water treated seaweed processing waste used in this study have moisture content values of 12.94±0.08% and 15.38±0.19%, ash content values of 16.72±0.08% and 18.39±0.19%, lignin content values of 15.38±0.11% and 12.74±0.38%, and cellulose content values of 26.92±0.57% and 34.57±0.81%, respectively. The result of SSF process of seaweed processing waste showed that different concentrations of T. reesei and S. cerevisiae (control, 5, 10, 15 and 20%) yielded significant effect (p0.05) on the total reducing sugars and ethanol produced. The Duncan Multiple Range Test (DMRT) showed that the treatment 10% of T. reesei and S. cerevisiae concentration in the seaweed processing waste treated with hot water was the best treatment producing highest yield of ethanol.